2005
DOI: 10.1364/josaa.22.000724
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a graded-index medium by use of subwavelength structures with graded fill factor

Abstract: We present a novel configuration for the implementation of subwavelength-based graded-index devices. The proposed concept is based on the etching of one-dimensional subwavelength gratings into a high-index slab waveguide to achieve the desired effective index distribution. A graded-index profile can be achieved by gradually modifying the duty ratio of the grating along the horizontal axis, while the beam is confined in the vertical direction by the slab waveguide. On the basis of this concept, novel graded-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 41 publications
0
40
0
1
Order By: Relevance
“…(35)] as well as the boundary condition at a small radius are satisfied by Eq. (26). Thus, the DEDT is exact for power-law graded spherical inclusions.…”
Section: Numerical Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…(35)] as well as the boundary condition at a small radius are satisfied by Eq. (26). Thus, the DEDT is exact for power-law graded spherical inclusions.…”
Section: Numerical Resultsmentioning
confidence: 87%
“…We have checked the exact solution [Eq. (26)] against the DEDT. We found that the differential equation [Eq.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 These features are useful for constructing polarization-selective beam splitters and general-purpose polarizationselective diffractive optical elements such as biréfringent computer-generated holograms. 36 Extending this concept to the 2D geometry or implementing aperiodicity enables other useful functionalities, such as converting a linear polarization state to radial or azimuthal polarization 39,40 and creating graded-index media. 40 ' 41 It was also shown that metamaterial approach can help to overcome fabrication difficulties and create a Fresnel lens analogue using binary lithographic fabrication with deep subwavelength feature sizes of less than 60 nm.…”
Section: Dielectric Metamaterialsmentioning
confidence: 99%
“…6 Furthermore, many artificially-graded-index optical metamaterials and elements have been fabricated nowadays. 7 Colloidal crystal has been extensively studied in nanomaterials engineering and its potential applications range from nanophotonics to chemistry and biomedicine. 8 It is desirable and of interest to use dielectric-coated metallic nanoparticles with varying shell thickness to form a dielectric constant gradient.…”
mentioning
confidence: 99%